The effect of the demarketing anti-smoking campaigns on tobacco package warning labels and its implications on the intention to quit smoking - Apryanus Fallo; Jou Sewa Adrianus; Maria Augustin Lopes Amaral (Junal Ilmu Manajemen, 2023)
Efforts or tools to permanently or temporarily reduce or maintain demand for consumption of certain products or services are defined as demarketing. The impact of this fact makes the government and the private sector have to use a demarketing scheme to deal with this situation. This study was conducted to determine the effect of anti smoking campaigns and tobacco package warning labels have an impact on attitude toward smoking and intention to quit smoking. This research is descriptive quantitive research with 150 respondents were collected by convenience sampling method. This study uses SEM AMOS Version 24 analyze to test the data. The result of this study is anti smoking campaigns has a positive significant to attitude toward smoking, tobacco package warning labels has a positive significant to attitude toward smoking, attitude toward smoking has a positive significant to intention toward smoking.